Dual-wavelength passively Q-switched erbium ytterbium codoped fiber laser based on a nonlinear polarization rotation technique - Sabran, M.B.S.; Jusoh, Z.; Babar, I.M.; Ahmad, Harith; Harun, Sulaiman Wadi (WILEY-BLACKWELL, 111 RIVER ST, HOBOKEN 07030-5774, NJ USA, 2015)
We report a room temperature all-fiber dual-wavelength Erbium Ytterbium codoped fiber laser (EYDFL) operating at 1543.3 and 1545.4 nm using a nonlinear polarization rotation (NPR) technique. An isolator is used in conjunction with a multilobed double-clad Erbium Ytterbium codoped fiber to induce intensity-dependent loss in a sufficiently high loss ring cavity to achieve dual-wavelength and Q-switching simultaneous operations. At the threshold pump power of 0.27 W, the EYDFL generates a sequence of pulses with repetition rate of 12.06 kHz and pulse width of 11.56 mu s. When the multimode pump is increased to 0.60 W, the repetition rate can be tuned to 57.94 kHz. The lowest pulse width of 5.04 mu s and the maximum pulse energy of 72.01 nJ are obtained at the pump power of 0.55 W. The simple and inexpensive dual-wavelength Q-switched NPR-based laser has a big potential for applications in metrology, environmental sensing, and biomedical diagnostics. (C) 2015 Wiley Periodicals, Inc.